(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper makes analyses of the World experience of using environmental factors in strengthening the economic potential of the regions of the Republic. On this case mythological aspects of the study has been pointed in different views. It concludes with the World experience of using environmental factors in strengthening the economic potential of the regions of the Republic